Equations balanced on the previous day | Equations balanced on the next day |
3 H2O + 3 Cl2 = 5 Cl{-} + ClO3{-} + 6 H{+}
Fe(H2O)6{3+} + Cl{-} = FeCl3 + H2O =>
Fe(H2O)6{3+} + 3 Cl{-} = FeCl3 + 6 H2O
Ph3COMgBr + HCl = Ph3COH + MgBr(Cl) =>
Ph3COMgBr + HCl = Ph3COH + MgBr(Cl)
H3C2N + O2 = CO2 + H2O + N2 =>
4 H3C2N + 11 O2 = 8 CO2 + 6 H2O + 2 N2
KOH + NH4NO3 = KNO3 + NH3 + H2O =>
KOH + NH4NO3 = KNO3 + NH3 + H2O
Sc2O3 = Sc2 + O3 =>
Sc2O3 = Sc2 + O3
CoO + H2SO4 = H2O + CoSO4 =>
CoO + H2SO4 = H2O + CoSO4
KMnO4 + H2S + H2SO4 = H2O + K2SO4 + MnO2 =>
8 KMnO4 + 3 H2S + H2SO4 = 4 H2O + 4 K2SO4 + 8 MnO2
Sn(OH)6{2-} + Si = HSnO2{-} + SiO3{2-} + H2O =>
2 Sn(OH)6{2-} + Si = 2 HSnO2{-} + SiO3{2-} + 5 H2O
AgNO3{-} + Na2PO4{3-} = Ag2PO4{3-} + NaNO3{-} =>
2 AgNO3{-} + Na2PO4{3-} = Ag2PO4{3-} + 2 NaNO3{-}
MnO + H2CO3 = MnCO3 + H2O =>
MnO + H2CO3 = MnCO3 + H2O
C10H20O + H2O = C10H22O2 =>
C10H20O + H2O = C10H22O2
ZnO + NaCl = ZnCl2 + Na2O =>
ZnO + 2 NaCl = ZnCl2 + Na2O
KNO3 + KOH = HNO3 + K2O =>
KNO3 + KOH = HNO3 + K2O
H2 + O2 = H2O =>
2 H2 + O2 = 2 H2O
Na3PO4 + Sn(NO3)4 = Sn3(PO4)4 + NaNO3 =>
4 Na3PO4 + 3 Sn(NO3)4 = Sn3(PO4)4 + 12 NaNO3
C3H6O + KMnO4 + H2SO4 = CH3COOH + MnSO4 + K2SO4 + H2O =>
10 C3H6O + 8 KMnO4 + 12 H2SO4 = 15 CH3COOH + 8 MnSO4 + 4 K2SO4 + 12 H2O
Al2O2 + NO2 + O2 + H2O = Al(NO3)3*9H2O =>
Al2O2 + 6 NO2 + 2 O2 + 18 H2O = 2 Al(NO3)3*9H2O
Cu(HSO4)2 + KOH = CuSO4 + K2SO4 + H2O =>
Cu(HSO4)2 + 2 KOH = CuSO4 + K2SO4 + 2 H2O
C7H9 + HNO3 = C7H6(NO2)3 + H2O =>
C7H9 + 3 HNO3 = C7H6(NO2)3 + 3 H2O
Al2(CO3)(s) = Al(s) + C(s) + O2(g) =>
2 Al2(CO3)(s) = 4 Al(s) + 2 C(s) + 3 O2(g)
Bi(OH)3 + HClO4 = Bi(ClO4)3 + H2O =>
Bi(OH)3 + 3 HClO4 = Bi(ClO4)3 + 3 H2O
C3H8 + O2 = CO2 + H2O =>
C3H8 + 5 O2 = 3 CO2 + 4 H2O
NaI + F = NaF3 + I3 =>
3 NaI + 9 F = 3 NaF3 + I3
SO3(g) = O2(g) + SO2(g) =>
2 SO3(g) = O2(g) + 2 SO2(g)
NaHCO3 = NaOH + CO2 =>
NaHCO3 = NaOH + CO2
CH3COOHC6H6 = CH3COOC6H7 =>
CH3COOHC6H6 = CH3COOC6H7
KClO3 + KJ + H2SO4 = J2 + KCl + K2SO4 + H2O =>
KClO3 + 6 KJ + 3 H2SO4 = 3 J2 + KCl + 3 K2SO4 + 3 H2O
TiOSO4 + H2O = H2TiO(SO4)2 + TiO2 =>
2 TiOSO4 + H2O = H2TiO(SO4)2 + TiO2